Effectiveness of a Process to Increase Ability in Self Care for the Elderly Living Alone in Rural Areas, Sukhothai Province - Tuntiwitayapan, Somkid; Tuntiwitayapan, Summana (Journal of Health Science of Thailand, 2017)
The objective of this study was to develop and examine the effectiveness of increased ability processes in self care behaviors (SCBs) for the elderly living alone in rural areas (ELARs). The study was conducted in 3 phases. The first phase aimed to assess factors predicting SCBs among the ELARs. The samples were 215 participants recruited by multistage random sampling. A questionnaire was administered by face to face interviews during December 2012 to March 2013; and analysis by Pearson’s product moment correlation coefficient and Stepwise multiples regression. The result showed that such variables as being supported by non-family members, perception of SCBs benefit, activities of daily living, supportive by health care providers, and health status, were found to make a unique contribution (up to 26%) to this prediction. The second phase was to construct a SCBs process for the ELARs which consisted of the study on needs and SCBs process suggested by stakeholders through six focus group discussions; and the content validity which was approved by five experts. The resulting SCBs process consisted of 3 steps: (1) the learning activities on the benefits of self care to reduce impact from aging and loneliness; (2) SCB modification; and (3) the activities to supportive SCBs from non-family members and local governmental organizations. The third phase was to evaluate effectiveness of SCBs; and it was found that there was a significant increase in the average score of SCBs after the intervention (p<0.05). Therefore, this SCB model should be applied and implemented for the elderly living alone in rural areas.